Is neck circumference an appropriate tool to predict cardiovascular risk in clinical practice? A cross-sectional study in Chilean population. Issue 11 (7th November 2019) - Caro, Patricia; Guerra, Ximena; Canals, Andrea; Weisstaub, Gerardo; Sandaña, Carlos
Abstract : Objectives: Neck circumference has emerged as a predictor of obesity and metabolic syndrome, but its clinical usefulness for different groups of population is not clearly defined. The aim is to evaluate the predictive capacity of neck circumference in order to detect cardiovascular risks (CVRs) on the Chilean population and to compare it with waist circumference performance. Design: Cross-sectional study. Setting: General Chilean population. Participants: Data of 4607 adults aged 18 and over from the Chilean National Health Survey 2009–2010 were analysed. Primary and secondary outcome measures: Anthropometrics measures included neck and waist circumference, height and weight. CVR was identified according to the Framingham tables adapted for the Chilean population. Receiver operating characteristics curves and logistic regression models were made to evaluate the performance of neck circumference to predict a moderate/high CVR, comparing it to waist circumference. Results: Almost 10% of the sample had a moderate or high CVR. The probability of having a moderate/high cardiovascular risk increase with cervical obesity (OR 1.95, 95% CI 1.04 to 3.68) and central obesity (OR 4.5, 95% CI 2.47 to 8.22). The area under the curves were high for cervical obesity (AUC 81.4%, 95% CI 78.8% to 84.0%) and central obesity (AUC 82.2%, 95% CI 79.7% to 84.7%) and not statistically different (p=0.152). Conclusions: Neck obesity has a high capacity to predict moderate/high CVR in the Chilean population. Its good performance appears as an opportunity to use it in clinical practice when waist circumference measurement is difficult to measure and eventually replace the waist circumference measurement as the technique is easier.